TINDAK PIDANA PENADAHAN DALAM HUBUNGANNYA DENGAN TINDAK PIDANA PENCURIAN - Mulyadi Wibowo (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACT Factors causing the crime of fencing include many factors the crime of theft; jeranya not factor in the theft offender committed the crime of theft: theft perpetrators are not caught factors, temperament factors (charakter) and environmental factors. The considerations that the judge used the course receive criminal. Sentence imposed is likely to be an advanced weight than if he was trying to help the judge to expedite the examination in the trial court. Criminal punishment against the fence is lighter than the thief, because in this case the thieves still get a profit by selling goods to the fence. Namely the pecuniary gain from the sale of fencing stolen goods. While a fence still have to buy and pay for it with money which turned out to be stolen goods. These are the factors in imposing sentence severity to be considered by a panel of judges who hear the case in relation to the theft and fencing.And then the author will address the criminal punishment of the perpetrators of the crime of fencing in the District Court against Samarinda.Penjatuhan criminal criminal criminal threats fencing is lighter than the theft. Therefore, the fence still must pay or fees for the goods that are fenced.